An evaluation of the blended pedagogy applied in the Municipal Minimum Competence Program: the case of Drakenstein and Mossel Bay - Odendaal, Liesel (Stellenbosch : Stellenbosch University, 2017)
Thesis (MPA)--Stellenbosch University, 2017.